ANALYSIS OF EDUCATION MANAGEMENT FACTORS IN THE EDUCATION SYSTEM AND EDUCATORS - Sudarno, Sudarno; Siswanto, Romi; Wahyuningsih, Rintatik (JURNAL PENDIDIKAN GLASSER, 2023)
One aspect that affects the activities of the learning process is the teacher, so that in order for the learning process to run well, the teacher must understand the material before it is delivered to students and know exactly the knowledge that students have at the beginning before attending the lesson. This study aims to determine the relationship between the education system and education management and educators with education management. The method of writing this scientific article is qualitative and literature study or Library Research. Reviewing literature books by the theory discussed, especially in Education Management, analyzing reputable scientific papers and essays from non-reputable journals. In qualitative research, a literature review must be used consistently with methodological assumptions. The result of this study is that the education system affects the administration/management of education. If the education management system is implemented, education will be better. Furthermore, educators have an important role in implementing education management so that education management develops even more.